2022
DOI: 10.2217/bmm-2022-0673
|View full text |Cite
|
Sign up to set email alerts
|

Serum Itih4 in Coronary Heart Disease: A Potential Anti-Inflammatory Biomarker Related to Stenosis Degree and Risk of Major Adverse Cardiovascular Events

Abstract: Aim: This study aimed to investigate the correlation of ITIH4 with inflammatory cytokines, stenosis degrees and prognosis in coronary heart disease (CHD) patients. Methods: Serum ITIH4 levels of 300 CHD patients and 30 controls, together with levels of TNF-α, IL-6, IL-8 and IL-17A of CHD patients, were determined using ELISA. Results: Serum ITIH4 was reduced in CHD patients versus controls (p < 0.001). ITIH4 was negatively linked with TNF-α, IL-6, IL-8, IL-17A, C-reactive protein, serum creatinine and Gensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Research on ITIH4 covers areas such as Sun et al ( 21 ) showed that ITIH4 is a key biomarker in the serum of patients with early gastric cancer and has potential as a high quality diagnostic marker for early gastric cancer. Huo et al ( 22 ). showed that serum ITIH4 may serve as an anti-inflammatory biomarker negatively associated with the degree of stenosis and the risk of major adverse cardiovascular events in patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…Research on ITIH4 covers areas such as Sun et al ( 21 ) showed that ITIH4 is a key biomarker in the serum of patients with early gastric cancer and has potential as a high quality diagnostic marker for early gastric cancer. Huo et al ( 22 ). showed that serum ITIH4 may serve as an anti-inflammatory biomarker negatively associated with the degree of stenosis and the risk of major adverse cardiovascular events in patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, elastin-derived peptide formation might prevent and/or delay atherosclerosis and T2D [ 82 ]. In line, proteomic analyses of aortas from DKO mice revealed upregulation of anti-inflammatory and atheroprotective markers and vasorelaxation mediators (ITIH4, LRP8/APOER2, MBL2, DBN1, PARK7/DJ-1) [ 83 87 ], whereas proteins related to the progression of atherosclerosis (DIAPH1) [ 88 ], foam cell formation and macrophage ferroptosis (IDH1) [ 89 ], and endothelial dysfunction and reactive oxygen species (ROS) production (XDH) [ 90 ] were downregulated. Thus, differential abundance of proteins associated with vasorelaxation and ROS production, downregulation of the ROS pathway, and myography data indicate that MMP12 deficiency improves endothelial dysfunction, which is considered an early stage in the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing body of data strongly supports the assumption that ITIH4 exerts a protective effect on injured cells, tissues, and organs by regulating JAK-STAT signaling 32 and nuclear factor kappa-B signaling. 33 Notably, circulating ITIH4 has potential as an anti-inflammatory biomarker for severity assessment and prognosis prediction in numerous diseases such as chronic obstructive pulmonary disease, coronary heart disease, rheumatoid arthritis, sepsis, and hepatitis C. [22][23][24][25][26] In five patients with acute ischemic stroke, there was a dominant downregulation of blood ITIH4 levels within 72 h after injury, which significantly increased when patients recovered. 27 In another group of acute ischemic stroke patients, serum ITIH4 levels immediately decreased at admission, gradually decreased until day 3, and then increased until day 30.…”
mentioning
confidence: 99%